Purinergic signaling: A gatekeeper of blood-brain barrier permeation - Wang, Yuemei; Zhu, Yuanbing; Wang, Junmeng; Dong, Longcong; Liu, Shuqing; Li, Sihui; Wu, Qiaofeng (Frontiers in Pharmacology, 2023)
This review outlined evidence that purinergic signaling is involved in the modulation of blood-brain barrier (BBB) permeability. The functional and structural integrity of the BBB is critical for maintaining the homeostasis of the brain microenvironment. BBB integrity is maintained primarily by endothelial cells and basement membrane but also be regulated by pericytes, neurons, astrocytes, microglia and oligodendrocytes. In this review, we summarized the purinergic receptors and nucleotidases expressed on BBB cells and focused on the regulation of BBB permeability by purinergic signaling. The permeability of BBB is regulated by a series of purinergic receptors classified as P2Y1, P2Y4, P2Y12, P2X4, P2X7, A1, A2A, A2B, and A3, which serve as targets for endogenous ATP, ADP, or adenosine. P2Y1 and P2Y4 antagonists could attenuate BBB damage. In contrast, P2Y12-mediated chemotaxis of microglial cell processes is necessary for rapid closure of the BBB after BBB breakdown. Antagonists of P2X4 and P2X7 inhibit the activation of these receptors, reduce the release of interleukin-1 beta (IL-1β), and promote the function of BBB closure. In addition, the CD39/CD73 nucleotidase axis participates in extracellular adenosine metabolism and promotes BBB permeability through A1 and A2A on BBB cells. Furthermore, A2B and A3 receptor agonists protect BBB integrity. Thus, the regulation of the BBB by purinergic signaling is complex and affects the opening and closing of the BBB through different pathways. Appropriate selective agonists/antagonists of purinergic receptors and corresponding enzyme inhibitors could modulate the permeability of the BBB, effectively delivering therapeutic drugs/cells to the central nervous system (CNS) or limiting the entry of inflammatory immune cells into the brain and re-establishing CNS homeostasis.